The Overview of Child development During the Covid-19 Pandemic - Dwi Astutiek; AV Sri Suhardiningsih; Damayanti Kusuma; Anies Listyowati; Sastro Sardjono (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
During the Covid-19 pandemic, various activities to stimulate young children suddenly stopped due to the emergency condition of the Covid-19 outbreak, However, the stimulation of growth and development for young children was quite ongoing and obtained quite good results by implementing the Covid-19 health protocol. The aims of this study is to describe the growth and development of children during the Covid-19 pandemic. The research method used is qualitative research with a phenomenological approach. The data collected is by means of participants observation and in-depth interviews through FGDs. The research results obtained are that children's growth and development can be seen by monitoring in the form of anthropometric measurements at the puskesmas or public health centers, as well as passive monitoring of growth and development as seen from the KIA’s handbook to prevent mass crowds as an effort to prevent the transmission of Covid-19 . The result in this study found that most were on the growth line in the KIA’s Handbook, while for the level of nutritional intake there were still some children who were lacking in nutrition. Most of the development of gross and fine motor skills in children is in accordance with the KIA’s handbook, however there are a few whose development is not in line with the KIA’s handbook, this could be due to one of the contributing factors, namely nutritional intake. In addition there are 44.44% of children experienced the negative impact of the pandemic on their children's mental-emotional condition, 33.33% of their mental-emotional condition was not affected due to the covid 19 pandemic and 22.22% did not provide clear information. Some of contributing factors that hinder children's growth and development, one of which are nutritional status , the cooperation with health care facilities , and also the support from parents to use educative indoor games and family recreation by implementing the Covid-19 health protocol.